(untitled) (Jurnal Ipteks Terapan, 2023)
This research was conducted to test the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), Return On Equity (ROE), and Market Share on stock returns on consumer good companies listed on the Indonesia Stock Exchange in 2019 – 2022 both partial and simultaneous. From a total population of 75 companies and based on the criteria specified determined that 33 sample companies were obtained during the last 5 years. This research is Quantitative research, the data studied is secondary data which is measured using a deep ratio scale statistical processing. The analysis technique used is multiple linear regression. Based on the results of data analysis using the t test (partial) DER, EPS and MARKET SHARE does not have a significant effect on stock returns, whereas ROA does significant positive influence on stock returns. Results of data analysis using F test (simultaneous) DER, ROA, EPS and MARKET SHARE simultaneously have a positive effect and significant to stock returns.